Integral Upbringing as the Fundamental Category of Practice and Theory of Pedagogy of Family in Christian Inspiration - Danuta Opozda (Nicolaus Copernicus University in Toruń, 2018)
The following article features the contents which indicate the outline of issues related to the category of 'integral upbringing' undertaken in the perspective of family pedagogy. They can be placed in two areas. The first one is focused on issues concerning integral development of family members and the special contribution of family to human development and integral upbringing. Conventionally speaking, it can be assumed that it is a direct subject of pedagogical reflection concerning the reality as well as the nature of married and family everyday life. The second area involves the questions about 'the category of integral upbringing' in the structure of family upbringing theory in the process of building knowledge about family.